2015
DOI: 10.1007/s00345-015-1732-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of klotho gene polymorphisms on urinary tract stone disease

Abstract: Any polymorphism altering the function of klotho gene may result with stone formation. We found that there are more GG sequences of G395A gene in patients with UTSD. That may be a polymorphism of klotho gene which results with stone formation. Further studies with more patients should be accomplished which are combining the genetic and epigenetic factors associated with urolithiasis and klotho gene to enlighten the etiology of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This gene is a type-1 transmembrane protein with glucuronidase activity that has a proposed role in renal calcium and phosphate homeostasis ( Telci et al, 2011 ). In five studies, ten Klotho gene variation was evaluated ( Telci et al, 2011 ; Xu et al, 2013 ; Gürel et al, 2016 ). Telci et al evaluated three SNPs in the Klotho gene and found the protective effect of rs3752472 on urolithiasis ( Telci et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene is a type-1 transmembrane protein with glucuronidase activity that has a proposed role in renal calcium and phosphate homeostasis ( Telci et al, 2011 ). In five studies, ten Klotho gene variation was evaluated ( Telci et al, 2011 ; Xu et al, 2013 ; Gürel et al, 2016 ). Telci et al evaluated three SNPs in the Klotho gene and found the protective effect of rs3752472 on urolithiasis ( Telci et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the rs3752472 polymorphism of the Klotho gene has a protective effect on the stone formation (OR:0.66; CI = 0.44–0.99) ( Xu et al, 2013 ). Gurel et al investigated the Klotho gene polymorphism and found that the rs1207568 variation has protective effects on the stone formation (OR:0.41; CI: 023–0.73) ( Gürel et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Klotho is an anti-aging protein and plays an important role in increasing life span [ 4 ]. It also plays an important role in suppressing various types of cancers [ 5 ], regulates calcium and phosphorus homeostasis [ 6 ], controls kidney functions and regulates cellular responses [ 4 ]. Some previous research also suggests a link between klotho and glucose metabolism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urolithiasis is affected by numerous factors, including genetic and environmental factors, abnormal metabolism, race, and living habits [ 5 ]; the specific mechanism by which urinary calculi form in Uighur children is still unknown. The single nucleotide polymorphisms are widely used to be a tool for identifying genetic alteration to map the complex disease genes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%